Capacity building among members of the Indonesian police during post- reform era - I.B. Wirawan and I.B Wirawan2, Moh. Nur Hidayat, (Opción, 2019)
This literature study is aimed at analyzing and explaining capacity building among members of the Indonesian Police during the post-reform era in the perspective of Democratic Policing within the Indonesian Police institution via comparative qualitative research methods. As a result, the Police is expected to be the guardians and drivers for democracy and its democratization process. Internal enlightenment is therefore required. It is because the Police’s duties have changed i.e., from politically, economically and technologically based duties into expansion and regional dynamics. In conclusion, modern training and training program include trainers and trainees who are focused on the learning process.